Cell shortening and calcium dynamics in epicardial and endocardial myocytes from the left ventricle of Goto‐Kakizaki type 2 diabetic rats. Issue 4 (25th February 2018) - Smail, Manal; Al Kury, Lina; Qureshi, Muhammad Anwar; Shmygol, Anatoliy; Oz, Murat; Singh, Jaipaul; Howarth, Frank Christopher
Abstract : New Findings: What is the central question of this study? To investigate haemodynamic dysfunction in the type 2 diabetic Goto‐Kakizaki (GK) rat, we measured shortening and Ca 2+ transport in ventricular myocytes from epicardial (EPI) and endocardial (ENDO) regions. What is the main finding and its importance? EPI and ENDO GK myocytes displayed similar hypertrophy. Time to peak (TPK) and time to half (THALF) relaxation were prolonged in EPI GK myocytes. TPK Ca 2+ transient was prolonged and THALF decay of the Ca 2+ transient was shortened in EPI GK myocytes. Amplitude of shortening, Ca 2+ transient and sarcoplasmic reticulum Ca 2+ were unaltered in EPI and ENDO myocytes from Goto‐Kakizaki compared with control rats. We demostrated regional differences in shortening and Ca 2+ transport in Goto‐Kakizaki rats. Abstract: Diabetic cardiomyopathy is considered to be one of the major diabetes‐associated complications, and the pathogenesis of cardiac dysfunction is not well understood. The electromechanical properties of cardiac myocytes vary across the walls of the chambers. The aim of this study was to investigate shortening and Ca 2+ transport in epicardial (EPI) and endocardial (ENDO) left ventricular myocytes in the Goto‐Kakizaki (GK) type 2 diabetic rat heart. Shortening and intracellular Ca 2+ transients were measured by video edge detection and fluorescence photometry. Myocyte surface area was increased in EPI‐GK and ENDO‐GK compared with control EPI‐CON and ENDO‐CON myocytes. Time to peak shortening was prolonged in EPI‐GK compared with EPI‐CON and in ENDO‐CON compared with EPI‐CON myocytes. Time to half‐relaxation of shortening and time to peak Ca 2+ transient were prolonged in EPI‐GK compared with EPI‐CON myocytes. Time to half‐decay of the Ca 2+ transient was prolonged in EPI‐CON compared with EPI‐GK and in EPI‐CON compared with ENDO‐CON myocytes. The amplitude of shortening and the Ca 2+ transient were unaltered in EPI‐GK and ENDO‐GK compared with their respective controls. Sarcoplasmic reticulum Ca 2+ and myofilament sensitivity to Ca 2+ were unaltered in EPI‐GK and ENDO‐GK compared with their respective controls. Regional differences in Ca 2+ signalling in healthy and diabetic myocytes might account for variation in the dynamics of myocyte shortening. Further studies will be required to clarify the mechanisms underlying regional differences in the time course of shortening and the Ca 2+ transient in EPI and ENDO myocytes from diabetic and control hearts. Abstract :